A Comparison of Single and Multifactor Portfolio Performance Methodologies - Chen, Nai-Fu; Copeland, Thomas E.; Mayers, David (Journal of Financial and Quantitative Analysis, 1987)
Nai-Fu Chen, Thomas E. Copeland, David Mayers, A Comparison of Single and Multifactor Portfolio Performance Methodologies, The Journal of Financial and Quantitative Analysis, Vol. 22, No. 4 (Dec., 1987), pp. 401-417